True Colors an analysis of the presentation of the themes and messages in the TV show Glee and the local audience reception of the show - Naguit, Jessica Therese Santos 1991-
"The researcher came up with the idea of conducting this study upon the realization than when watching episodes of Glee she disregards the carefree way it addressed certain social issues which she usually finds repulsive. This study seeks to show how the presentation of the different social issues in Glee affects the acceptance of the audience. It also aims to understand the role of Filipino values in this acceptance. Qualitative methods were used to gather the necessary data for the study. Textual analysis was used to identify the social issues often discussed in Glee and how these issues are presented in the show. A focused interview was conducted on teenagers regarding their views on the seven social issues that the study focused on. These issues are as follows: bullying, blackmail, underage drinking, teenage pregnancy, sex education and celibacy, extra-marital affairs and acceptance of gays and lesbians. After the focused interview, four episodes of Glee which heavily featured the social issues were viewed by the repondents. Finally a focused group discussion was conducted to determine the level of acceptance by the respondents on the way the social issues were presented in the show. Framing theory was used to analyze both the text, which the show Glee, and the response of the audience. The study concluded that Filipino values do influence the acceptance or rejection of the Filipino audience towards the presentation of social issues in Glee."